Relapse of autoimmune diseases after liver transplantation - V. E. Syutkin; A. A. Salienko; O. D. Olisov; M. S. Novruzbekov (Трансплантология (Москва), 2022)
Background. The recurrence of autoimmune liver diseases can lead to reduced survival of recipients and grafts.Aim. To study the incidence and impact of the recurrence of autoimmune liver diseases on graft survival; the effect of maintenance immunosuppression on the recurrence of autoimmune diseases in liver transplant recipientsMaterial and methods. Transplantation outcomes in 111 recipients (21 recipients operated on for autoimmune hepatitis, 50 recipients operated on for primary biliary cirrhosis, and 40 recipients operated on for primary sclerosing cholangitis) were analyzed retrospectively.Results. The recurrence of autoimmune hepatitis is observed in 5%, the recurrence of primary biliary cirrhosis is in 10%, and the recurrence of primary sclerosing cholangitis is in 17% of cases. Among patients with recurrence of autoimmune diseases, men accounted for 54%, while for only 31% in the subgroup of patients without relapse (p=0.004). The followup for recipients with relapse (64.5 (42.8;82.0) months) was comparable to the follow-up for recipients without relapse (46.5 (17.9;103.5) months, p=0.54). A ten-year graft survival was significantly higher in the group of recipients with recurrent autoimmune diseases compared with recipients without autoimmune diseases recurrence (p<0.0001).Conclusions. The recurrence of autoimmune diseases leads to a decrease in graft survival. The effect of immunosuppression components on the risk of recurrence of autoimmune diseases in the graft has not been established.